2018
DOI: 10.1128/mbio.01088-18
|View full text |Cite
|
Sign up to set email alerts
|

Segregation but Not Replication of the Pseudomonas aeruginosa Chromosome Terminates at Dif

Abstract: Segregation of genetic information is a central event in cellular life. In bacteria, chromosome segregation occurs concurrently with replication, sequentially along the two arms from oriC to dif. How the two processes are coordinated is unknown. We explored here chromosome segregation in an opportunistic human pathogen, Pseudomonas aeruginosa, using its strain with markedly unequal chromosomal arms. We found that replication and segregation diverge in this strain and terminate at very different locations, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…A major feature differing genomes of PAO1 derivatives MPAO1 and PAO1-DSM, is the lack of a large inversion resulting from the homologous recombination between two rRNA operons rrnA and rrnB [5], which is present in the reference PAO1-UW genome [7]. Despite an asymmetrical positioning of the dif region in PAO1-UW, this inversion does not seem to affect chromosome segregation and such large rearrangements might be common among bacteria [8]. Remarkably, recent analyses indicated that sequence variation including singlenucleotide polymorphisms (SNPs), multiple-nucleotide polymorphisms (MNPs) and indels could lead to major variations in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A major feature differing genomes of PAO1 derivatives MPAO1 and PAO1-DSM, is the lack of a large inversion resulting from the homologous recombination between two rRNA operons rrnA and rrnB [5], which is present in the reference PAO1-UW genome [7]. Despite an asymmetrical positioning of the dif region in PAO1-UW, this inversion does not seem to affect chromosome segregation and such large rearrangements might be common among bacteria [8]. Remarkably, recent analyses indicated that sequence variation including singlenucleotide polymorphisms (SNPs), multiple-nucleotide polymorphisms (MNPs) and indels could lead to major variations in e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent experiments were carried out with cells grown in minimal medium, with replication initiated only once per cell cycle. The oriC-proximal region was tagged with tetO repeats and visualized using a fluorescent repressor operator system (FROS) as previously described (27,28). Its location was followed in parental PAO1-UW cells and in cells deficient in one or both condensins.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate this possibility, we explored chromosome segregation in condensin mutants using marker frequency analysis. To this end, chromosomal DNA of the mutant cells was subjected to deep sequencing, and the relative abundances of genomic loci fit to a model that postulates up to two replication start events at the oriC during the lifetime of the cell (28). This analysis quantifies duplication of genomic loci following the passage of a replication fork, which leads to a higher copy number of origin-proximal DNA fragments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Mycobacterium smegmatis, the oriC was found to be localized slightly off-center with respect to midcell (18). In Pseudomonas aeruginosa (19), the origin is localized at the cell center, as observed in E. coli (1). In the case of Streptomyces coelicolor, multiple copies of linear chromosomes have been demonstrated in hyphal cells (20).…”
mentioning
confidence: 84%